Influence of foodservice quality on customer satisfaction in the universities of Klang Valley, Malaysia: locals vs internationals - Salehuddin, Nadzirah; Othman, Mohhidin; Abdul Karim, Muhammad Shahrim; Ghazali, Hazrina (Tourism Educators Association of Malaysia, 2012)
University foodservices in Malaysia have long been catering to the day-to-day meals for their students and staff of differing cultural backgrounds. As an educational tourism centre, higher education institutions in Malaysia continue to attract a large number of international students to further their studies. Since internationals and local Malaysians have different perspectives over the quality of services provided by on-campus foodservices, operators are faced with the exceptional challenge of fulfilling the needs of both unique groups simultaneously. Therefore, the aim of this study is to compare local and international customers in terms of their expectations and perceptions of university foodservice. The sampling frame for the study was students and staff of universities and colleges from around the Klang Valley area, with the survey administered between September and December 2011. The data was analysed using frequency, paired sample t-test, multiple regression and independent sample t-test analyses. The study revealed that there was no significant relationship between customer satisfaction and the respondents’ country of origin; thus there were no differences between locals and internationals in terms of customer satisfaction with university foodservices. The data also indicated that both ‘Product Quality’ and ‘Value to Customer’ have significant effects on customer satisfaction of both locals and international respondents, with ‘Technological Application’ as an additional determinant for local customers. This paper will contribute significantly towards a deeper insight into the differences in satisfaction levels and the specific needs of these unique groups of clientele, thus aiding university foodservice operators in providing better service to all their customers, whether local or international.